Participatory communication as a key strategy in the construction of citizenship - Incio, Felipe Anderson Rios; Navarro, Enaidy Reynosa; Arellano, Edith Gissela Rivera; Meléndez, Lindon Vela (Linguistics and Culture Review, 2021)
This research set out to analyze the importance of participatory communication as a critical strategy in the construction of citizenship through an exhaustive review of the specialized literature; whose purpose was to update the knowledge related to citizenship and its structure, participatory communication and its contribution to the construction of citizenship, as well as updated approaches to participatory communication. The scientific information supporting the study results was fundamentally extracted from scientific journals indexed in Scopus, Web of Science, Scielo, Redalyc, and Dialnet. All citations and bibliographic references were managed using Mendeley. As preliminary results, it is found that participatory communication facilitates the integration and cohesion of the communities, based on joint projects, decision-making, participation, and actions that benefit citizens. It is concluded that citizenship is in constant change depending on the citizen; also, that it is essential to recover the relationship between citizenship and participation in pursuit of socio-cultural development; likewise, that community participation must be legitimate, holistic, and inclusive; also, that the contribution of communication lies in the dynamization of social actors; finally, that participatory communication approaches make it possible to dynamize the determining social behaviors to achieve social empowerment.